2019
DOI: 10.1073/pnas.1806838116
|View full text |Cite
|
Sign up to set email alerts
|

Activin-like kinase 5 (ALK5) inactivation in the mouse uterus results in metastatic endometrial carcinoma

Abstract: The endometrial lining of the uterine cavity is a highly dynamic tissue that is under the continuous control of the ovarian steroid hormones, estrogen and progesterone. Endometrial adenocarcinoma arises from the uncontrolled growth of the endometrial glands, which is typically associated with unopposed estrogen action and frequently occurs in older postmenopausal women. The incidence of endometrial cancer among younger women has been rising due to increasing rates of obesity, a major risk factor for the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 55 publications
1
39
0
Order By: Relevance
“…Recent work has shown that dysregulation of TGFb signaling in the mouse uterus results in endometrial cancer (44,45). Members of the TGFb signaling pathways were targeted by a number of dysregulated miRNAs.…”
Section: Dicer1 -/Cells (Supplementarymentioning
confidence: 99%
“…Recent work has shown that dysregulation of TGFb signaling in the mouse uterus results in endometrial cancer (44,45). Members of the TGFb signaling pathways were targeted by a number of dysregulated miRNAs.…”
Section: Dicer1 -/Cells (Supplementarymentioning
confidence: 99%
“…Unfortunately, the etiology of endometrial cancer remains poorly defined, hampering the design of effective diagnostic and therapeutic options for this disease. In PNAS, two exciting studies from the Matzuk laboratory (2,3) elegantly demonstrate that transforming growth factor β (TGF-β) signaling maintains endometrial homeostasis by suppressing cell overgrowth and oncogenesis. This action, the researchers show, is achieved through the TGF-β type I receptor (TGFBR1, or ALK5) and SMAD2/3.…”
mentioning
confidence: 99%
“…Although mutation of the pathway components accounts for only a very small percentage of endometrial cancer, alteration in the signaling activity may be a common contributing factor (7)(8)(9)(10)(11)(12). To determine whether TGF-β signaling is involved in uterine physiology and cancer development, the Matzuk team took advantage of the Cre-loxP approach by generating mice with conditional knockout (cKO) of Alk5 [Monsivais et al (2)] or Smad2/3 [Kriseman et al (3)] in the uterus (Alk5 cKO or Smad2/3 cKO mice, respectively). The researchers used progesterone receptor (Pgr) Cre recombinase, which deletes genes in uterine epithelial, stromal, and myometrial cells (2,3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent publications in PNAS (1,2) describe the phenotypic effects of loss of activin-like kinase 5; transforming growth factor β receptor 1 (ALK5;TGFBR1) or Smad2 and Smad3 in the mouse uterus and are accompanied by a commentary by Li (3). Our conclusions are that this pathway acts as a tumor suppressor pathway, findings that are also supported by a recent paper (4).…”
mentioning
confidence: 99%